Prolonged repeated-sprint ability is related to arterial O2 desaturation in men - Billaut, F.; Smith, K. (International Journal of Sports Physiology and Performance, 2010)
The ability to repeatedly generate maximum power output is usually accompanied by neuromuscular adjustments. Purpose: This study aimed to explore the occurrence of arterial O2 desaturation during prolonged repeated-sprint ability (RSA) testing and its relationship to neuromuscular activity, as evidenced by changes in surface integrated electromyogram (iEMG). Methods: Fifteen, national-level soccer players performed twenty 5-s cycle sprints (25 s of rest). Mechanical work and surface iEMG of the vastus lateralis (VL) and rectus femoris (RF) of the dominant lower limb were recorded for every sprint. Arterial O2 saturation (SpO2) was estimated via pulse oximetry and rating of perceived exertion (RPE) recorded immediately after every sprint. Results: Over the sprints, mechanical work (23.5%), iEMG (VL: 14.2%, RF: 16.4%) and SpO2 (3.5%) decreased, and RPE progressed to 19 (all P < .05). There was a strong linear relationship (R2 = .83, P < .05) between the changes in mechanical output and iEMG during the sprints. More importantly, changes in SpO2 accompanied changes in mechanical work, iEMG and RPE (R2 = .68, R2 = .64, R2 = .62, P < .05, respectively). Conclusion: The study suggests that in a homogenous group of athletes a progressive arterial O2desaturation develops during a prolonged RSA test, which may contribute toward performance regulation via an effect on sense of effort and neuromuscular activity.